(untitled) (Global Journal of Human-Social Science, 2023)
The Congolese State for several decades through a crisis of self-management This crisis deeply affects all sectors of national life and does not allow it to play a significant influence on the national continental or international scene The foreign presence in the Democratic Republic of Congo and the pressures of the international community in the face of the democracy desired by it could be justified not only in a political but also in an economic context It is a question of imposing in a political but also economic context It is a question of imposing the leaders who must allow the great powers to illegally exploit natural resources and to impose Western ideology